ASSOCIATIONS OF THE ANGIOTENSIN GENE POLYMORPHISM (AGT, RS699) WITH SYSTEMIC HYPERTENSION AND ITS RISK FACTORS IN GORNAYA SHORIA INHABITANTS - T. A. Mulerova; A. V. Ponasenko; A. V. Tsepokina; A. A. Kuzmina; M. Yu. Ogarkov (Российский кардиологический журнал, 2017)
Aim. To assess the prevalence  of polymorphism of the gene  AGT and its relation with systemic  hypertension  risk in the  ethnicities  of Gornaya  Shoria (Mountain Shoria).Material and methods. A clinical-epidemiological study conducted, of compactly inhabiting people of uneasily reachable areas of Gornaya Shoria (settlements Orton, Ust-Kabyrza) and city-like settlement Sheregesh. Based  on the name  lists, 1178 inhabitants included from the settlements. In 398 persons, blood was collected from cubital vein, fasting, in the morning for genotyping. Extraction of DNA from the blood was done with phenol-chloroform  method.  Polymorphism of AGT (М235Т, rs699) gene was tested with PCR.Results. In general,  in both  ethnicities,  the  prevalence  of AGT  did not  differ significantly. However, among  men there was national specifics found for the C/C genotype:  in the Shortsy group  its prevalence  (27,8%) was higher comparing  to non-native inhabitants (10,3%). In shortsy male cohort the carriers of T/C had odds ratio for glucose metabolism and arterial hypertension at 2,45 and 2,21, respectively; in females with C/C carriage  the risk of dyslipidemia was 3,37. Among females of non-native  nationality  there   were  associations  found  for  T/T  genotype   with hypercholesterolemia. The odds  ratio for higher cholesterol  among  homozygotes T-allele was 4,3 times higher comparing to T/C and C/C.Conclusion. Regardless the absence of differences  in genotypes prevalences of AGT, there were differences  revealed  of the association  of risk factors  of arterial hypertension   according   to  ethnicity.  In shortsy  cohort  the  C/C  genotype   was associated with hyperbetacholesterolemia and dyslipidemia, and genotype  T/C — with glucose  metabolism.  In non-native cohort T/T genotype  was associated with dyslipidemia.